Dimensi Islam dan Politik: Telaah Historis atas Revolusi Iran 1979 - Mundzir, Chaerul (Al-Hikmah, 2020)
Abstract The article discusses the contact between Islam and politics in the history of Iran’s upheaval between 1960-1979. The authoritarian stance of the Shah Pahlavi dynasty and its proximity to the United States caused a wave of protest against it. The wave of protests led by Ayatullah Khomeini gave rise to a political movement known in history as the Iranian Revolution in 1978. This revolution succeeded in overthrowing the Shah Pahlavi dynasty and the establishment of the Islamic Republic of Iran in 1979. The existence of the Islamic Republic of Iran made several form of change in the political structure of the country. The existence of institutions such as the Wilayatul Faqih and the Guardian Council in the Iranian structure is proof of the harmony between Islam and politics in the State of the Mullahs. Keywords: Iran, Revolution, Republic, Khomeini Abstrak Artikel ini membahas persentuhan antar Islam dan politik dalam sejarah pergolakan Iran dalam tahun 1960-1979. Sikap otoriter masa pemerintahan Dinasti Syah Pahlevi serta kedekatannya dengan Amerika Serikat menyebabkan gelombang protes atas bermunculan. Gelombang protes yang dimotori oleh oleh Ayatullah Khomeini memunculkan sebuah gerakan politik yang terkenal dalam sejarah dengan nama Revolusi Iran pada tahun 1978. Revolusi tersebut berhasil menumbang Dinasti Syah Pahlevi dan menjadi awal berdirinya Negara Republik Islam Iran pada tahun 1979. Eksistensi Negara Republik Islam Iran menjadi wujud perubahan dalam struktur politik negara tersebut. Keberadaan lembaga seperti Wilayatul Faqih dan Dewan Wali dalam struktur pemerintahan Iran menjadi bukti harmoni antara Islam dan politik di Negara para Mullah tersebut. Keywords : Iran, Revolusi, Republik, Khomeini Abstract The article discusses the contact between Islam and politics in the history of Iran’s upheaval between 1960-1979. The authoritarian stance of the Shah Pahlavi dynasty and its proximity to the United States caused a wave of protest against it. The wave of protests led by Ayatullah Khomeini gave rise to a political movement known in history as the Iranian Revolution in 1978. This revolution succeeded in overthrowing the Shah Pahlavi dynasty and the establishment of the Islamic Republic of Iran in 1979. The existence of the Islamic Republic of Iran made several form of change in the political structure of the country. The existence of institutions such as the Wilayatul Faqih and the Guardian Council in the Iranian structure is proof of the harmony between Islam and politics in the State of the Mullahs. Keywords: Iran, Revolution, Republic, Khomeini Abstrak Artikel ini membahas persentuhan antar Islam dan politik dalam sejarah pergolakan Iran dalam tahun 1960-1979. Sikap otoriter masa pemerintahan Dinasti Syah Pahlevi serta kedekatannya dengan Amerika Serikat menyebabkan gelombang protes atas bermunculan. Gelombang protes yang dimotori oleh oleh Ayatullah Khomeini memunculkan sebuah gerakan politik yang terkenal dalam sejarah dengan nama Revolusi Iran pada tahun 1978. Revolusi tersebut berhasil menumbang Dinasti Syah Pahlevi dan menjadi awal berdirinya Negara Republik Islam Iran pada tahun 1979. Eksistensi Negara Republik Islam Iran menjadi wujud perubahan dalam struktur politik negara tersebut. Keberadaan lembaga seperti Wilayatul Faqih dan Dewan Wali dalam struktur pemerintahan Iran menjadi bukti harmoni antara Islam dan politik di Negara para Mullah tersebut. Keywords : Iran, Revolusi, Republik, Khomeini